Atrial fibrillation and use of antithrombotic medications in older people: A population-based study. (15th December 2017) - Ding, Mozhu; Fratiglioni, Laura; Johnell, Kristina; Fastbom, Johan; Ljungdahl, Maria; Qiu, Chengxuan
Abstract: Background: Trends in the use of antithrombotic drugs in elderly patients with atrial fibrillation (AF) are largely unknown. We estimated the prevalence of AF in an older population, and examined whether use of anticoagulant and antiplatelet drugs in older AF patients has changed over time. Methods: Data from the population-based Swedish National study on Aging and Care in Kungsholmen ( n = 3363, age ≥ 60 years, 64.9% women) were used (2001–2004 and 2007–2010). AF cases were identified through 12-lead electrocardiogram, physician examinations, and patient register records (ICD-10 code I48). We used the CHADS2 and CHA2 DS2 -VASc scores to estimate stroke risk, and an incomplete HAS-BLED score to estimate bleeding risk. Results: At baseline (2001–2004), 328 persons (9.8%) were ascertained to have AF. The prevalence of AF increased significantly with age from 2.8% in people aged 60–66 years to 21.2% in those ≥ 90 years, and was more common in men than in women (11.2% vs. 9.0%). Among AF patients with CHADS2 score ≥ 2 at baseline, 25% were taking anticoagulant drugs and 54% were taking antiplatelet drugs. High bleeding risk was significantly associated with not using anticoagulant drugs in AF patients (multi-adjusted OR = 2.50, p = 0.015). Between 2001–2004 and 2007–2010, use of anticoagulant drugs increased significantly, especially in AF patients with CHA2 DS2 -VASc score ≥ 2 (23% vs. 33%, p = 0.008) and in those with HAS-BLED score < 3 (32% vs. 53%, p = 0.004). Conclusion: AF is common among old people. The use of anticoagulant drugs increased over time in AF patients, yet still two-thirds of those with high stroke risk remained untreated.